2022
DOI: 10.3390/cancers14040883
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Is a Circulating Prognostic Biomarker for Hepatocellular Carcinoma Patients Treated with Combined Immunotherapy

Abstract: Atezolizumab/bevacizumab (Atezo/Bev) combination therapy has become a front-line therapy for advanced hepatocellular carcinoma (HCC), but approximately 20% of patients are nonresponders. We investigated circulating biomarkers to predict therapeutic outcomes. We performed simultaneous measurement of 34 proteins using a multiplex bead-based immunoassay in baseline plasma from 34 patients who underwent Atezo/Bev therapy as first- or second-line treatment. Logistic regression analysis showed that plasma IL-6 and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 32 publications
3
47
0
Order By: Relevance
“…Previous reports have shown that many adipomyokines are secreted by skeletal myocytes or adipocytes, including muscle growth inhibitors (interleukin-6 [IL-6], myostatin, activins A/B, growth, and differentiation factor 15) and muscle growth promoters (follistatin, irisin, bone morphogenetic protein [BMPs], and brain-derived neurotrophic factor) [ 28 ]. Myojin et al [ 29 ] recently reported that the PFS and OS of the IL-6-high group were significantly shorter than those of the IL-6-low group of patients with advanced HCC treated with atezolizumab plus bevacizumab. Further investigation into the association between SMI decrease and adipomyokine concentrations is required.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that many adipomyokines are secreted by skeletal myocytes or adipocytes, including muscle growth inhibitors (interleukin-6 [IL-6], myostatin, activins A/B, growth, and differentiation factor 15) and muscle growth promoters (follistatin, irisin, bone morphogenetic protein [BMPs], and brain-derived neurotrophic factor) [ 28 ]. Myojin et al [ 29 ] recently reported that the PFS and OS of the IL-6-high group were significantly shorter than those of the IL-6-low group of patients with advanced HCC treated with atezolizumab plus bevacizumab. Further investigation into the association between SMI decrease and adipomyokine concentrations is required.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating soluble factors, such as cytokines, have been evaluated as biomarkers over the course of ICI therapy [ 25 ]. An evaluation of the baseline levels of 34 circulating serum cytokines and chemokines of patients receiving Atezolizumab plus Bevacizumab highlighted that only interleukin 6 (IL-6) and interferon alpha (IFN-alpha) were related to disease progression [ 26 ]. IL-6 is an inflammatory cytokine involved in liver regeneration, but also shows an oncogenic role [ 27 , 28 ], as it is involved in the recruitment of myeloid-derived suppressor cells, thereby favoring tumor immune escape [ 29 ].…”
Section: Traditional Non-invasive Biomarkers Of Response To Icismentioning
confidence: 99%
“…IL-6 is an inflammatory cytokine involved in liver regeneration, but also shows an oncogenic role [ 27 , 28 ], as it is involved in the recruitment of myeloid-derived suppressor cells, thereby favoring tumor immune escape [ 29 ]. It can be simply detected by an enzyme-linked immunosorbent assay (ELISA) [ 25 , 26 ].…”
Section: Traditional Non-invasive Biomarkers Of Response To Icismentioning
confidence: 99%
“…HCC has a high recurrence rate and many patients eventually require systemic therapy. Owing to the great success of multiple recent clinical trials, six systemic therapy regimens are currently available for treating unresectable HCC (u-HCC); these therapies include the use of tyrosine kinase inhibitors, anti-vascular endothelial growth factor receptor 2 (VEGFR2) antibody and combination immunotherapy [ 2 ]. Notably, based on the IMbrave150 trial, atezolizumab, anti-programmed cell death1-ligand1 (PD-L1) antibody, and bevacizumab, anti-vascular endothelial growth factor (VEGF) antibody combination immunotherapy (Atezo/Bev) was recently approved and serves as a standard treatment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, although an objective response was observed in 30% of patients, 19% of treated patients were reported to be nonresponsive [ 3 ]. We have also recently reported that approximately 30% of u-HCC cases were initially refractory to Atezo/Bev therapy in a real-world setting [ 2 , 5 ]. Currently, there is no reliable biomarker for predicting HCC patients who will fail to benefit from combination immunotherapy.…”
Section: Introductionmentioning
confidence: 99%